ASSOCIATION AND AUTHORITY: Lancashire Baptists, 1765-18651. (July 2013) - Clark, Cullen
Abstract : The Evangelical Awakening led to renewed interest in associationalism among Baptists. The Lancashire and Yorkshire Baptist Association and the later Lancashire and Cheshire Association illustrate the extent to which authority, if any, was exercised over local churches as well as the freedoms they maintained.